Balancing Agility and Formalism in Software Engineering Second IFIP TC 2 Central and East European Conference on Software Engineering Techniques, CEE-SET 2007, Poznan, Poland, October 10-12, 2007, Revised Selected Papers - Meyer, Bertrand; Nawrocki, Jerzy R.; Walter, Bartosz; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the thoroughly refereed post-conference proceedings of the Second IFIP TC 2 Central and East Conference on Software Engineering Techniques, CEE-SET 2007, held in Poznan, Poland, in October 2007. The 21 revised full papers presented together with 2 keynote addresses were carefully reviewed and selected from 73 initial submissions. The papers are organized in topical sections on measurement, processes, UML, experiments, tools, and change.
Keynotes -- Agile Software Development at Scale -- Formalisms in Software Engineering: Myths Versus Empirical Facts -- Measurement -- Extending GQM by Argument Structures -- On Metamodel-Based Design of Software Metrics -- Automatic Transactions Identification in Use Cases -- Processes -- A Collaborative Method for Reuse Potential Assessment in Reengineering-Based Product Line Adoption -- Corporate-, Agile- and Open Source Software Development: A Witch$1 (Bs Brew or An Elixir of Life? -- Capable Leader and Skilled and Motivated Team Practices to Introduce eXtreme Programming -- UML -- Platform-Independent Programming of Data-Intensive Applications Using UML -- Towards UML-Intensive Framework for Model-Driven Development -- UML Static Models in Formal Approach -- Experiments -- Does Test-Driven Development Improve the Program Code? Alarming Results from a Comparative Case Study -- Measuring the Human Factor with the Rasch Model -- Empirical Analysis of a Distributed Software Development Project -- Tools -- Extending Software Architecting Processes with Decision-Making Activities -- A Tool for Supporting Feature-Driven Development -- In-Time Role-Specific Notification as Formal Means to Balance Agile Practices in Global Software Development Settings -- Best Papers Session -- An Integrated Approach for Identifying Relevant Factors Influencing Software Development Productivity -- A Framework for QoS Contract Negotiation in Component-Based Applications -- A Case Study on the Impact of Refactoring on Quality and Productivity in an Agile Team -- Change -- Modeling of Requirements Tracing -- Support for Cooperative Design of End-User Tailorable Software -- Manifoldness of Variability Modeling $1 (BConsidering the Potential for Further Integration.s
Keywords: Computer science; Software engineering; Data structures (Computer science).; Computers; Application software; Management information systems; Computer Science; Software Engineering/Programming and Operating Systems; Data Structures, Cryptology and Information Theory; Theory of Computation; Software Engineering; Management of Computing and Information Systems; Computer Appl. in Administrative Data Processing; Electronic books